2002
DOI: 10.1289/ehp.021101191
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated ambient air particles induce vasoconstriction of small pulmonary arteries in rats.

Abstract: The objective of this study was to determine whether short-term exposures to concentrated ambient particles (CAPs) alter the morphology of small pulmonary arteries in normal rats and rats with chronic bronchitis (CB). Sprague-Dawley male rats were exposed to CAPs, using the Harvard Ambient Particle Concentrator, or to particle-free air (sham) under identical conditions during 3 consecutive days (5 hr/day) in six experimental sets. CB was induced by exposure to 276 +/- 9 ppm of sulfur dioxide (5 hr/day, 5 days/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(67 citation statements)
references
References 54 publications
3
61
0
2
Order By: Relevance
“…1). Most notably, several studies in humans and animals have shown significant arterial vasoconstriction following PM inhalation [28,37]. The altered autonomic balance may be playing a direct role in mediating this vasoconstriction and thereby the BP elevation.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…1). Most notably, several studies in humans and animals have shown significant arterial vasoconstriction following PM inhalation [28,37]. The altered autonomic balance may be playing a direct role in mediating this vasoconstriction and thereby the BP elevation.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…The importance of considering CAPs composition rather than CAPs mass concentration has been highlighted in several reports from our laboratory (Clarke et al 2000b;Batalha et al 2002;Saldiva et al 2002). ST-segment elevation was found to be related to a specific component Fig.…”
Section: Components Of Ambient Air Pollution In Myocardial Ischemiamentioning
confidence: 88%
“…For example, in CAPs-exposed dogs, increases in bronchoalveolar lavage neutrophil percentage, circulating neutrophils and lymphocytes, and total peripheral white blood cell counts were significantly associated with an aluminum/silicon factor (Clarke et al 2000a). Batalha et al (2002) observed that the degree of pulmonary vascular vasoconstriction was strongly correlated with the elemental concentration of silicon in normal and bronchitic rats exposed to CAPs. These observations suggested that components of ambient particles whose concentrations vary in parallel with the concentration of silicon may be highly toxic.…”
Section: Components Of Ambient Air Pollution In Myocardial Ischemiamentioning
confidence: 94%
“…Children exposed to ambient PM demonstrate elevated plasma ET -1 and mean pulmonary arterial pressure (Calderon -Garciduenas et al, 2007 ). Inhalation of urban PM has been demonstrated to increase vascular tone in small pulmonary arterioles (Batalha et al, 2002 ). This process appears, in part, to be a consequence of altered NO -mediated vasorelaxation.…”
Section: Endothelial Cellsmentioning
confidence: 99%